The impact of adhering to masculine norms on the relationship between job satisfaction and life satisfaction - Nepute, Jeff, author; Dik, Bryan, advisor; Swaim, Randall, committee member; Richards, Tracy, committee member; Miller, Lisa, committee member (Colorado State University. Libraries, 2014)
Job satisfaction (JS) has been shown to significantly predict life satisfaction (LS) across a large array of research (Tait, Padgett, & Baldwin, 1989), though the strength of the relationship varies (Steiner & Truxillo, 1987). Authors have suggested the difference in the strength of the relationship across studies may be due to the presence of moderators (Rain, Lane, & Steiner, 1991), particularly an individual's level of work importance (Lent & Brown, 2008). Unfortunately, the research on the moderating impact of work importance uses measures which lack sufficient validity and reliability evidence about their scores (Steiner & Truxillo, 1987). Steiner and Truxillo (1987) suggested Kanungo's ( 1982) Work Importance Questionnaire and Job Importance Questionnaire as a specific measure which would address this concern, though adherence to traditional masculine norms may also tap into the construct of work importance. Individuals who adhere to traditional masculine norms of the dominant culture in the U.S. often place even greater emphasis on their work role (Mahalik et al., 2003). The past literature on adherence to masculine norms has generally focused solely on negative outcomes (Kiselica & Englar-Carlson, 2010) and often samples including only mainly White, heterosexual men (Parent & Smiler, 2012). The current study explores the impact of potential moderators on the relationship between job and life satisfaction, examines how this relationship may vary across categories of identity, evaluates potential positive outcomes of adherence to masculine norms, and analyzes how adherence to masculine norms may vary across categories of identity. An online survey was given to 290 U.S. adults, working at least part time, about job satisfaction, life satisfaction, positive and negative affect, job and work importance, and adherence to masculine norms. The results showed job satisfaction to predict life satisfaction, though did not find any significant moderating effect of any measure of work importance (work importance, job importance, primacy of work). The model explaining the largest amount of variance (45%) suggested that job satisfaction may have an indirect effect on life satisfaction, through positive and negative affect. The above results did not vary by gender (job satisfaction predicting life satisfaction, no significant moderators, mediation model). With regard to adherence to masculine norms, there were no relationship detected between positive outcomes and adherence. While the current sample did not have sufficient numbers to examine how adherence to masculine norms may vary by ethnicity and sexual orientation, differences between men and women were examined. Men showed significantly higher adherence to masculine norms, as well as higher adherence to specific norms of power over women, the use of violence, and frequently changing sexual partners. The results suggest the need for more complex models and statistical methods, using outside raters, selecting methods that can test causality, and intentionally selecting higher numbers of ethnic and sexual minorities. With regard to clinical implications, the study suggests the need to address values around help-seeking, focusing on strengths for adherence to masculine norms, and addressing barriers within therapy and barriers towards entering therapy for individuals with high self-reliance.
Keywords: masculine norms; life satisfaction; masculinity; conformity to masculine norms; job satisfaction